The Anthropocene as a challenge for sociological thinking in planetary dimensions - Block, Katharina (DIE ERDE – Journal of the Geographical Society of Berlin, 2022)
In this article, I argue for the relevance of integrating the planetary dimension, which is at the heart of the Anthropocene debate, into sociological thinking. The argumentation takes place in two steps: first, by sounding out the Anthropocene debate in search of the few sociological considerations that explicitly treat the significance of the Anthropocene for the architecture of sociological theory and theory formation, highlighting the associated desideratum within sociology which concerns the planetary dimension of the Anthropocene and the question of integrating it in sociological thinking; second, by following Dipesh Chakrabarty in outlining initial thoughts on why the planetary dimension should be integrated into sociology as a constitutive of the social and thus as a fundamental category of social theory. For this, I will also refer to Gesa Lindemann’s conceptualization of social theory, which clarifies the systematic function of social theory in the architecture of sociological thinking. The aim of the article is also to sensitize for the possibility of interdisciplinary collaborations of knowledge creation in light of the awareness for the planetary dimension of social life.